Workaholism profiles: Associations with determinants, correlates, and outcomes - Gillet, N.; Morin, A.; Cougot, B.; Gagné, Marylène (BPS Journals Department, 2017)
The present series of studies examines how the two dimensions of workaholism (working excessively and compulsively) combine within different profiles of workers. This research also documents the relations between these workaholism profiles and a series of correlates (psychological need thwarting) and adaptive and maladaptive work outcomes. In addition, this research investigates the role of emotional dissonance and employees' perceptions of their workplaces' psychosocial safety climate (Study 1, n = 465), as well as job demands, resources, and perfectionism (Study 2, n = 780) in the prediction of profile membership. Latent profile analysis revealed four identical workaholism profiles in both studies. In Study 1, emotional dissonance predicted a higher likelihood of membership in the Very High, Moderately High, and Moderately Low profiles relative to the Very Low profile. In contrast, Study 2 revealed a more diversified pattern of predictions. In both studies, levels of need thwarting were the highest in the Very High and Moderately High profiles, followed by the Moderately Low profile, and finally by the Very Low profile. Finally, in both studies, the most desirable outcomes levels (e.g., lower levels of work–family conflict and emotional exhaustion, and higher levels of perceived health) were associated with the Very Low profile, followed by the Moderately Low profile, then by the Moderately High profile, and finally by the Very High profile. Practitioner points: The most desirable outcomes are associated with the profile characterized by the lowest levels of workaholism. Emotional dissonance predicts a lower likelihood of membership in the profile characterized by the lowest levels of workaholism. Levels of need thwarting are the lowest in the Very Low workaholism profile. High levels of socially prescribed perfectionism are associated with an increased likelihood of membership into the Very High workaholism profile. Reducing emotional dissonance, need thwarting, and socially prescribed perfectionism may help to reduce workaholism, in turn leading to more positive outcomes.